Modeling Spray C and Spray D with FGM within the framework of RANS and LES - Di Matteo, Andrea; Bao, Hesheng; Somers, Bart (Frontiers in Mechanical Engineering, 2022)
In the current paper, two different diesel-like igniting sprays, the Engine Combustion Network (ECN) Spray C and D configurations, are investigated. In particular, the study focuses on the respective performance of RANS and LES in predicting a turbulent igniting spray using the OpenFOAM platform. Breakup model, discretization schemes and case setups, including the combustion model, are kept the same to discard any potential effect on the simulation except for the intrinsic differences due to the turbulence modeling. For the RANS approach, a classic κ-ε model has been applied, and for the LES approach, a dynamic structure model has been used to close the momentum equation. The κ-ε model constants are tuned to obtain a good prediction of the inert experiments. Both approaches provide a reasonable agreement to the inert experiments regarding the global spray characteristics, the liquid length and the vapor penetration. However, transient local properties, including the spatial distribution of mixture fraction variance and species distributions, are not identical. In reacting conditions the Flamelet Generate Manifold (FGM) model has been adopted in both LES and RANS, using several enthalpy levels as the 4th dimension in the tabulation to account for local heat-loss. The results report a good agreement of the two turbulence models with experimental data, in terms of liquid length and vapor penetration and lift off length, while a slight short ignition delay is registered for both sprays and turbulence frameworks. Key role is found to be played by turbulence-chemistry interaction (TCI), here considered via a presumed probability density function (β-PDF) applied to the mixture fraction, in the reproduction of species distribution in the domain.